Bacillus marmarensis sp nov., an alkaliphilic, protease-producing bacterium isolated from mushroom compost - KAZAN, DİLEK (MICROBIOLOGY SOC, 2010)
A Gram-stain-positive, obligately alkaliphilic bacterium designated strain GMBE 72(T) was isolated from mushroom compost from Yalova, located in the Marmara region of Turkey. Cells were aerobic, straight rods and they formed subterminal to terminal ellipsoidal endospores. The isolate was catalase-positive, oxidase-negative and motile and contained a type A1 gamma peptidoglycan based on meso-diaminopimelic acid. The strain grew at pH 8.0-12.5. The major cellular fatty acid was anteiso-C-15:0. The genomic DNA G+C content was 40.2 mol%. Phylogenetic analyses based on 16S rRNA gene sequencing showed that strain GMBE 72(T) belonged to the genus Bacillus and exhibited 98.2% sequence similarity to Bacillus pseudofirmus DSM 8715(T). DNA-DNA reassociation was 56% between GMBE 72(T) and B. pseudofirmus DSM 8715(T). According to our polyphasic characterization, strain GMBE 72(T) represents a novel species of the genus Bacillus, for which the name Bacillus marmarensis sp. nov. is proposed. The type strain is GMBE 72(T) (=DSM 21297(T) =JCM 15719(T)).
Keywords: POINT-OF-VIEW; ALKALITOLERANT BACTERIUM; OBLIGATE ALKALIPHILE; ALKALINE PROTEASES; SEQUENCE ALIGNMENT; STRAINS; REIDENTIFICATION; PROPOSAL; LIMITS; ACID